Le projet 'Epistolart' a la lumière de cinq lettres évoquant Léonard de Vinci (Quaderni di Gargnano, 2018)
This piece accompanies the “EpistolART” project for the digital reissue of Carteggio inedito d’artisti dei secoli XIV, XV e XVI originally published in 1839-1840 by J.W. Gaye. It reproduces five letters concerning Da Vinci’s activities in Milan in 1506 and conducts a textual analysis that highlights the problems intrinsic to Gaye’s editorial criteria, which do not correspond to modern philological standards. Although the Gaye edition is familiar to art historians, the new study can still offer new insights into the work, living conditions and language of a Renaissance artist, even one so extensively studied as Leonardo da Vinci.
Keywords: Leonardo da Vinci; Gaye; letters; edition